The Impact of the Evolving Human Immunodeficiency Virus Response on the Epidemiology of Tuberculosis in South African Children and Adolescents. (3rd February 2021) - du Preez, Karen; Osman, Muhammad; Seddon, James A; Naidoo, Pren; Schaaf, H Simon; Munch, Zahn; Dunbar, Rory; Mvusi, Lindiwe; Dlamini, Sicelo S; Hesseling, Anneke C
Abstract: Background: Few studies have evaluated tuberculosis control in children and adolescents. We used routine tuberculosis surveillance data to quantify age- and human immunodeficiency virus (HIV)-stratified trends over time and investigate the relationship between tuberculosis, HIV, age, and sex. Methods: All children and adolescents (0–19 years) routinely treated for drug-susceptible tuberculosis in South Africa and recorded in a de-duplicated national electronic tuberculosis treatment register (2004–2016) were included. Age- and HIV-stratified tuberculosis case notification rates (CNRs) were calculated in four age bands: 0–4, 5–9, 10–14, and 15–19 years. The association between HIV infection, age, and sex in children and adolescents with tuberculosis was evaluated using multivariable logistic regression. Results: Of 719 400 children and adolescents included, 339 112 (47%) were 0–4 year olds. The overall tuberculosis CNR for 0–19 year olds declined by 54% between 2009 and 2016 (incidence rate ratio [IRR] = 0.46; 95% confidence interval [CI], .45–.47). Trends varied by age and HIV, with the smallest reductions (2013–2016) in HIV-positive 0–4 year olds (IRR = 0.90; 95% CI, .85–.95) and both HIV-positive (IRR = .84; 95% CI, .80–.88) and HIV-negative (IRR = 0.89; 95% CI, .86–.92) 15–19 year olds. Compared with 0- to 4-year-old males, odds of HIV coinfection among 15–19 year olds were nearly twice as high in females (adjusted odds ratio [aOR] = 2.49; 95% CI, 2.38–2.60) than in males (aOR = 1.35; 95% CI, 1.29–1.42). Conclusions: South Africa's national response to the HIV epidemic has made a substantial contribution to the observed declining trends in tuberculosis CNRs in children and adolescents. The slow decline of tuberculosis CNRs in adolescents and young HIV-positive children is concerning. Understanding how tuberculosis affects children and adolescents beyond conventional age bands and by sex can inform targeted tuberculosis control strategies. Abstract : We studied trends in tuberculosis case notification rates (2004–2016) in South African children and adolescents and explored associations between tuberculosis, age, HIV and sex. Age- and HIV-stratified analyses identified adolescents and young HIV-positive children as particularly vulnerable groups.